O pensamento algébrico e sua propositura no material EMAI do estado de São Paulo para o ciclo de alfabetização (1º ao 3º ano) - Marcondes, Rianne Schutzer Luiz (2023)
This dissertation highlight the results found throughout the development of the master's research, linked to the Professional Graduate Program in Education, at the Federal University of São Carlos (PPGPE/UFSCar). As an objective, we sought to analyze the declared conception about the perspective of work with algebraic thinking present in the material "Mathematics Education in the initial years" (EMAI) adopted by the State Education Network of São Paulo (SP), as well as the nature of the tasks that involve him in the literacy cycle (1st to 3rd year). For this, we started with an initial mapping of Professional Graduate Programs in the state of São Paulo and events in Mathematics Education (ENEM and EPEM) for the analysis of existing productions on the subject, thus fulfilling the stage of "Literature review". In addition, we constitute the "Theoretical Reference" in the field of studies on curriculum, curriculum in Mathematics Education and algebraic thinking. This research presents a methodological approach of a qualitative nature, with a descriptive-analytical-interpretative character. The central instrument for data production adopted was the documental analysis of the EMAI material, mainly the nature of the mathematical tasks that involved algebraic thinking. The results obtained showed that the EMAI material, with regard to the literacy cycle, presents approximately 59 tasks that involve objects of knowledge and skills of the thematic unit Algebra, as proposed by the National Common Curricular Base (BNCC) and Currículo Paulista, however, if the teacher cannot understand what is being asked, he will not explore them in their potential and will not develop algebraic thinking with the students. This fact demonstrates the need to invest in continuing education for these professionals, since it is challenging to work on aspects of algebraic thinking in the early years, as they did not have contact with this theme in their initial training. As a result of this research, an Educational Product was created in digital book mode (e-book) entitled "Children's Literature and Mathematics: proposals for tasks involving algebraic thinking for the literacy cycle", which presents possibilities of mathematical problematization with the unit Algebra theme in the first years of schooling.